Small bowel heterotopic gastric mucosa as a lead point for recurring intussusception - Justin C. Dourado; Anne Fischer (Elsevier, 2021)
Heterotopic gastric mucosa (HGM) can be discovered anywhere along the gastrointestinal tract but is a rare entity beyond the ligament of Treitz in the absence of Meckel's Diverticulum. These lesions are often asymptomatic and there have been very limited reports of HGM alone presenting as intussusception. In the few cases presented, most utilized a 99 mTc pertechnetate scan (Meckel's scan) or intraoperative palpation of the small bowel to aid in identification of the HGM. We present a case of a 6-year-old male with a total of six episodes of recurrent intussusception caused by an ileal islet of HGM with no pathologic lead point identified over multiple modalities of investigation including one prior manual evaluation of the small bowel. The current literature regarding the diagnosis and management of these lesions is reviewed and a proposed algorithm for patients with recurrent intussusception is presented.